OP91 Informal caregiving and markers of adiposity in the uk household longitudinal study. (2nd September 2017) - Lacey, R; McMunn, A; Webb, E
Abstract : Note: Presentation moved to health inequalities 2 session on wednesday Background: Providing informal care is known to be associated with poorer psychological health. However less is known about other, more objective health outcomes such as adiposity. The aim of this study was to investigate associations between being an informal caregiver with measures of adiposity using a large, representative UK longitudinal study. Methods: Data on 20 669 participants of the UK Household Longitudinal Study were used to explore the relationship between caregiving and adiposity (body mass index (BMI) and waist circumference). We additionally investigated caregiving intensity (hours spent caregiving per week, number of people cared for and combining caregiving with paid work). Multiple imputation was used to account for missing data. Associations between caregiving and adiposity measures were tested using multivariable linear regressions. Analyses were stratified by gender and interactions with age were tested. Models adjusted for household income, educational attainment, social class, presence of a long-standing limiting illness, number of dependent children in the household and partnership status. All analyses included survey weights to account for design, unequal probabilities of selection, differential non-response and potential sampling errors. The analyses were conducted in Stata v14. Results: Being an informal caregiver was associated with increased waist circumference (1.48 cm, 95% CI: 0.42, 2.53) but not BMI for men in age-adjusted models. Women who were informal carers had higher waist circumferences (3.62 cm, 95% CI: 2.77, 4.47) and BMIs (1.26, 95% CI: 0.89, 1.64) relative to non-carers. A caring-age interaction was present for women suggesting that younger women carers (aged 16–44) had particularly higher waist circumferences (5.44 cm, 95% CI: 3.77, 7.10) and BMIs (1.90 cm, 95% CI: 1.17, 2.62). Caregiving intensity was found to be important with increasing hours of caregiving associated with increasing adiposity. Discussion: Being an informal carer was associated with increased adiposity amongst UK men and women. Caring appears to be particularly negatively associated with adiposity when occurring during non-normative life stages, such as early adulthood, and when high intensity. These findings are based on nationally representative longitudinal data. The main limitation of this study was the inability to investigate the reasons the care recipient requires care (i.e. dementia vs cancer), and to investigate the mechanisms involved. Given funding cuts for social care, advancements in medical treatment and increasing life expectancy, a greater proportion of the population will be expected to provide informal care for relatives and friends. The poorer health of carers should therefore be a priority for UK public health.